2012
DOI: 10.2147/ijn.s29290
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-loaded magnetic nanoparticles for breast cancer therapeutics and imaging applications

Abstract: Background:The next generation magnetic nanoparticles (MNPs) with theranostic applications have attracted significant attention and will greatly improve nanomedicine in cancer therapeutics. Such novel MNP formulations must have ultra-low particle size, high inherent magnetic properties, effective imaging, drug targeting, and drug delivery properties. To achieve these characteristic properties, a curcumin-loaded MNP (MNP-CUR) formulation was developed. Methods: MNPs were prepared by chemical precipitation metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(30 citation statements)
references
References 62 publications
3
27
0
Order By: Relevance
“…In this study, we demonstrate improved anti-cancer efficacy of PLGA-CUR NPs with in vitro and in vivo tumorigenic assays (Figure 2–4). The improved anti-cancer efficacy of our PLGA-CUR NP formulation is in accordance with previous studies [16, 49]. It is thought that NP formulations are more effective due to the sustained drug release over time compared to the short exposure to free CUR.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, we demonstrate improved anti-cancer efficacy of PLGA-CUR NPs with in vitro and in vivo tumorigenic assays (Figure 2–4). The improved anti-cancer efficacy of our PLGA-CUR NP formulation is in accordance with previous studies [16, 49]. It is thought that NP formulations are more effective due to the sustained drug release over time compared to the short exposure to free CUR.…”
Section: Discussionsupporting
confidence: 91%
“…However, clinical translation of CUR is substantially hindered due to poor pharmacokinetics and insufficient bioavailability at the primary tumor as well as metastatic sites. Incorporating CUR into a nanoformulation may be very useful for patient treatment and is a viable option [14, 16]. Curcumin nanoformulations may target tumor tissue through either passive or active mechanisms that will improve its activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These magnetic nanoparticles have shown increased reactive oxygen species levels in prostate cancer cells and lower cell viability leading to enhanced cell death and increased expression of NF-κB in DU145 cells (Sato et al, 2013). Recent studies suggest that multi-layer magnetic nanoparticle system(s) has been highly encouraged due to their theranostic (therapy and imaging/diagnosis) applications in cancer (Yallapu et al, 2013b; Yallapu et al, 2010a; Yallapu et al, 2012b; Yallapu et al, 2011). Yazdi et al (Yazdi et al, 2012) synthesized a magnetic nanoparticle loaded with docetaxel which showed higher cytotoxicity than the free drug in cancer cells and this delivery system can be used to inhibit development of resistance in cancer cells.…”
Section: Using Nanotechnology To Overcome Docetaxel Resistancementioning
confidence: 99%
“…From this it can be considered that oleic acid layered magnetic NPs have enriched lipoproteins and albumin while complement and immunoglobulin proteins likely escape the immune system and RES. With this in mind, we have generated oleic acid/cyclodextrin layers with Pluronic polymer stabilizers for delivery of curcumin/doxorubicin [75, 76]. …”
Section: Curcumin Nanoparticles-plasma Protein Corona In Cancer Thmentioning
confidence: 99%